Select Illinois community college elected trustees' perspectives on how prepared they are to serve their term of office - Winfree, Terri L., author; Kuk, Linda, advisor; Davies, Timothy, committee member; Banning, James, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2012)
Community college trustees are officials entrusted by the public to oversee the resources and property of community colleges; the board of trustees is seen as the link between the institution and the community they serve. Trustees make decisions that affect every aspect of an institution; therefore the accountability of these individuals at the local and state level is a high priority. The purpose of this study was to explore how prepared Illinois community college trustees are for their role as an elected official. The study explored trustees' understanding of their college's mission and culture, and the principles that shape higher education. An emphasis was placed on their responsibilities related to public trust and the interests of their constituencies. And finally, the study explored whether trustees feel their past experiences have prepared them, and if professional development will assist them, in their role as a trustee. Findings indicated that when a person decides to run for the office of a community college trustee many do not realize the magnitude of the commitment they are making. Stewardship was important and engagement, at the appropriate level, was also very important. Trustees should make strong ethical commitments to their organizations, their constituents, their values, and to the work of leadership. While doing so they should also understand the difference between the role of a trustee and the role of college administrators. There is the need for internal orientations so trustees have an understanding of how different departments of a college operate and are funded. Trustees agreed that organized professional development activities are a true value and trustees would benefit with participation. Many licensed professionals are required to participate in continuing education, and while trustees are not licensed professionals, they are entrusted to make decisions that affect stakeholders financially, personally, and professionally.
Keywords: trustee; board governance; community college; elected; leadership; professional development